Controlled growth of titanium dioxide nanotubes for doxorubicin loading and studies of in vitro antitumor activity - Zhang, Yunshan; Huang, Tuo; Lv, Wanwan; Yang, Kai; Ouyang, Cuiling; Deng, Minxin; Yi, Rongyuan; Chu, Hui; Chen, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium dioxide (TiO2) materials are suitable for use as drug carriers due to their natural biocompatibility and nontoxicity. The aim of the study presented in this paper was to investigate the controlled growth of TiO2 nanotubes (TiO2 NTs) of different sizes via an anodization method, in order to delineate whether the size of NTs governs their drug loading and release profile as well as their antitumor efficiency. TiO2 NTs were tailored to sizes ranging from 25 nm to 200 nm according to the anodization voltage employed. The TiO2 NTs obtained by this process were characterized using scanning electron microscopy, transmission electron microscopy, and dynamic light scattering The larger TiO2 NTs exhibited greatly improved doxorubicin (DOX)-loading capacity (up to 37.5 wt%), which contributed to their outstanding cell-killing ability, as evidenced by their lower half-maximal inhibitory concentration (IC50). Comparisons were carried out of cellular uptake and intracellular release rates of DOX for large and small TiO2 NTs loaded with DOX. The results showed that the larger TiO2 NTs represent a promising therapeutic carrier for drug loading and controlled release, which could improve cancer treatment outcomes. Therefore, TiO2 NTs of larger size are useful substances with drug-loading potency that may be used in a wide range of medical applications.